A formação em curso Técnico em Enfermagem sob a ótica do egresso em um centro estadual de educação profissional no oeste do Paraná - Menegarde, Marivania (2021)
Secondary level technical professional education is one of the spaces less explored by research in the educational field compared to others, such as fundamental education and higher education. It is in this field that training takes place to work in various professions, including nursing. General objective: to evaluate the training offered in the technical course in nursing at a State Center for High School Technical Education, from the perspective of the graduate and as specific objectives to outline the profile of graduates from the technical school; identify how they evaluate the teaching-learning process experienced in the course; evaluate, from the perspective of the graduates, the training received in relation to their professional performance. Case study, supported by an exploratory, descriptive study with a quantitative and qualitative approach. Quantitative data were collected through an online questionnaire with open and closed questions and sent by messaging app to graduates between 2014 and 2018. Qualitative data were obtained through interviews with open questions sent by messaging app, for two students each semester, randomly drawn from the list of graduates. Quantitative data were systematized in tables and analyzed descriptively, and qualitative data were systematized by content analysis in the form of thematic analysis. Two articles resulted from the systematization and analysis process. Article 1: "Evaluation of graduates on training in the technical nursing course of a state professional education center" responded to the objectives of the study and shows that the graduates are mostly married women, under 40 years of age, who have managed to work until six months after completing the course in private hospitals; most subjects were considered sufficient for professional practice, with percentages above 80%. In the qualitative data, the themes were systematized: technical training is a passport to entry into the world of work; from technical training to integral human training; the role of teachers in training and the things that could be different in the technical nursing course. It concluded that training was sufficient and decisive in the lives of graduates for insertion and permanence in work, showing the importance of public spaces for technical training in nursing. Article 2, entitled “The good teacher in the perception of graduates of a course for nursing technicians” aimed to highlight the perceptions of nursing technicians about what a good teacher is. The themes were systematized: the good teacher and his attitudes; the good teacher is the one who masters what he teaches and the good teacher masters teaching methods. This article concludes the complexity of being a good teacher, as it involves extrinsic and intrinsic motivations that affect you and, in this context, a professional needs to be built. The results show that the school fulfills its role in the social context, forming professionals who are accepted in the world of work and with prepared teachers.